Drug resistance and Mycobacterium tuberculosis strain diversity in TB/HIV co-infected patients in Ho Chi Minh city, Vietnam. (September 2017) - Mai, Trinh Quynh; Van Anh, Nguyen Thi; Hien, Nguyen Tran; Lan, Nguyen Huu; Giang, Do Chau; Hang, Pham Thi Thu; Lan, Nguyen Thi Ngoc; Marais, Ben J.; Sintchenko, Vitali
Highlights: TB/HIV co-infection in Vietnam was associated with high rates of TB drug resistance and likely community transmission of drug resistant strains. The vast majority of isoniazid resistant strains in Vietnam have high-level isoniazid resistance in HIV (+) patients. Beijing is the predominant lineage among TB/HIV co-infected patients; but EAI-5 is specifically overrepresented compared to HIV (−) patients. The variety of drug resistance profiles and phylogenetic diversity of strains do not suggest high rates of nosocomial transmission. Abstract: Background: Mycobacterium tuberculosis strain diversity and drug resistance among people living with human immunodeficiency virus (HIV) in Vietnam have not been described previously. Methods: We examined M. tuberculosis isolates from TB/HIV co-infected patients in Ho Chi Minh City, Vietnam. Drug susceptibility testing (DST), spoligotyping and 24-locus Mycobacterial Interspersed Repetitive Unit (MIRU-24 typing) were performed, and the rpoB, katG, inhA and inhA promoter, rpsL, rrs and embB genes were sequenced in all drug resistant isolates identified. Results: In total, 84/200 (42.0%) strains demonstrated "any drug resistance"; 17 (8.5%) were multi-drug resistant (MDR). Streptomycin resistance was present in 80 (40.0%) isolates; 95.2% (80/84) with "any drug resistance" and 100% with MDR. No rifampicin monoresistance was detected. Of the rifampicin resistant strains 16/18 (88.9%) had mutations in the 81-bp Rifampicin Resistance Defining Region (RRDR) of the rpoB gene. Isoniazid resistance was mostly associated with Ser315Thr mutations in the katG gene (15/17; 88.2%). Beijing (49.0%) and East African Indian (EAI) lineage strains (35.0%; 56/70 EAI-5) were most common. Conclusion: TB/HIV co-infection in Vietnam was associated with high rates of TB drug resistance, although we were unable to differentiate new from retreatment cases.